Outcomes of “sandwich” chemoradiotherapy compared with chemotherapy alone for the adjuvant treatment of FIGO stage III endometrial cancer - Wang, Shao-Jing; Wang, Lily; Sun, Lou; Shih, Yu-Hsiang; Hsu, Shih-Tien; Liu, Chin-Ku; Hwang, Sheau-Feng; Lu, Chien-Hsing (Frontiers in Oncology, 2022)
Objective To analyze and compare outcomes of adjuvant chemoradiotherapy in patients with International Federation of Gynecology and Obstetrics (FIGO) stage III endometrial cancer (EC) patients using the “Sandwich” sequence and chemotherapy (CT) alone. Methods From 2005 to 2019, we retrospectively reviewed 80 patients with FIGO stage III EC who received treatment at our institute. We analyzed 66 patients who had undergone complete surgical staging followed by adjuvant treatment with sandwich chemoradiotherapy (39 patients) and CT alone (27 patients). The 5-year overall survival (OS), progression-free survival (PFS), and disease-specific survival (DSS) were calculated using the Kaplan-Meier method. Additional prognostic factors were analyzed using Cox proportional hazards regression. Results Herein, the analysis was conducted using 66 patients with a median follow-up period of 50 and 85 months in the sandwich and CT alone arms. Comparing the sandwich sequence and CT alone groups, the 5-year OS and PFS 87% vs. 70% (p=0.097) and 77% vs. 65% (p=0.209), respectively. The sandwich therapy conferred an improved 5-year DSS (92% vs. 70%, p=0.041) and a lower local recurrence rate (0% vs. 11%, p=0.031). In multivariable analyses, grade 3 histology and deep myometrial invasion were independent risk factors for 5-year OS and DSS. The sandwich sequence was a positive predictor for 5-year DSS (hazard ratio [HR]=0.23, p=0.029). The sandwich arm demonstrated higher acute hematologic toxicity than the CT alone arm. CT dose delay/reduction and treatment completion rates were similar in both groups. Conclusion For patients with stage III EC, post-operative sandwich chemoradiotherapy appears to offer a superior 5-year DSS and local control with tolerable toxicity when compared with CT alone.